Study the Facts and Truth on the Levels of Conflict Disasters and Victims: In the Case of Amhara and Afar-Ethiopia - Damtew, Alie Wube; Ejigu, Asamen Ayalew (Ethiopian Journal of Social Sciences, 2023)
The objective of this study was to investigate the facts and truth about the levels of displaced, damaged,and victims of the current Ethiopian conflict in general and the Amhara and Afar Regions in particular.The investigations mainly used exploratory qualitative methods and a combination of primary andsecondary sources of data. Field surveys, figures, photographs, and cause and effect (fish bone-diagram)analysis supplemented the qualitative data. 382 responses were considered for these investigations fromthe target area. The study shows that many civilians were killed in the current conflicts between TPLFforces and the Ethiopian government in the Amhara and Afar regions of northern Ethiopia. Theinvestigation shows that the TPLF has killed many innocent people, including civilians in the Amhara andAfar regions, and others have been seriously injured. Due to the TPLF-led forces, the elderly, women,youths, and children might be the first victims of the current situation in Amhara and Afar regions,considering their especially vulnerable position. Damaged and pillaged institutions, towns, and otherpublic organizations such as churches, mosques, market places, educational centers, health centers, andmanufacturing industries are affecting Amhara and Afar from all walks of life as well. Because of thedistraction of various public institutions, government organizations, and public service centers, millions ofAmhara and Afar people faced unemployment and social disruption. This study also shows the variouscauses, results, and outcomes of the current conflicts from scientific viewpoints using the cause and effectdiagram. Finally, the conclusion and the recommendations of the study were incorporated into this study.